Hubungan Asupan Protein dengan Kejadian Wasting pada Balita - Yesvi Zulfiana; Nurul Fatmawati; Yopi Suryatim Pratiwi (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2024)
Nutritional status is a condition of the body resulting from food consumption and use of nutrients. Riskesdas data in 2013 shows that West Nusa Tenggara has a fairly high prevalence of malnutrition, namely 25.7% of the national standard. Wasting is an acute malnutrition problem that can indirectly increase the risk of morbidity and death in children under 5 years of age. Currently, wasting is still a serious public health problem with a prevalence rate of 11.1% in Indonesia. One of the factors causing disruption of nutritional status can be seen directly. This study aims to determine the relationship between protein intake and the incidence of wasting in toddlers. Cross sectional research was conducted on 100 respondents selected through a household survey. Data was collected through observation and interviews with respondents. The results of this study show a relationship between protein intake and the incidence of wasting in toddlers as seen from the BW/TB indicator. It is necessary to provide guidance on increasing nutritional intake, especially protein intake, and handling infectious diseases in toddlers so that malnutrition can be managed well.